Design of a tuned mass damper for damped structures using an orthogonal-function-based equivalent linearization method. (December 2020) - Ghaffarzadeh, Hosein; Younespour, Amir; Cheng, Shaohong
Abstract: One of the most popular strategies of dissipating vibration energy in engineering structures is to use vibration absorbers. The selection of optimum absorber parameters is extremely important, especially for tuned mass dampers (TMD). Various approximate and numerical methods have been proposed to determine the optimum tuning ratio of a TMD attached to a damped linear structure, of which the application is limited either to lightly damped structures or specific forms of external excitation. In particular, the latter constrains the implementation of these existing methods to many practical engineering problems where the external excitations are typically random. In the current study, a new approach of identifying the optimum tuning ratio of a TMD in a damped primary linear structure is proposed based on an orthogonal-function-based equivalent linearization (EL) method. The effectiveness of the proposed TMD design approach is evaluated by numerical examples and two benchmark buildings. Results show that the proposed method cannot only accurately choose the optimum parameters of a TMD, but is also applicable to a structure having a relatively high mass and/or damping ratio and is subjected to random external excitations. The proposed method is an alternative approach to tune the TMD for damped structures, in methodological terms.